+0  
 
0
54
1
avatar

Find the integer $n$ satisfying $\dfrac{{(n + 1)!\, - 3(n - 1)!}}{{(n + 1)!\, + 3(n - 1)!}} = \dfrac{{53}}{{59}}$ .

 Jan 20, 2021
 #1
avatar+116126 
+1

Cross-multiply

 

59  [ ( n + 1)!  - 3(n - 1)!  ] =   53 [ (n + 1)!  +3 (n - 1)! ]

 

(59 - 53)(n + 1)!   =  (59*3 + 53*3) ( n -1)!

 

6(n + 1)!   =  336  ( n -1)!

 

(n + 1)!  / ( n -1)!  =   336   / 6

 

(n + 1)!  / ( n -1)!   = 56                     [ note :    (n + 1)!   / (n - 1)!    =  (n + 1) n  ]

 

(n + 1) n     = 56

 

8 * 7   =  56

 

n  = 7

 

cool cool cool

 Jan 20, 2021

69 Online Users

avatar
avatar
avatar